POSITION RESOURCES IN THE COASTAL AREA OF KHANH HOA PROVINCE: POTENTIAL AND PROSPECTS - Trang, Trinh Thi Minh; Ha, Nguyen Thi Nguyet; Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2015)
Coastal area in Khanh Hoa Province belongs to Coastal South Central Region, where the Vietnam mainland juts out farthest into the west of the East Sea, and has a special relationship in space with the offshore Spratly islands, the geo-strategic Highlands and economic - political centre of Ho Chi Minh City. This coastal area is close to the sloping and deep continental shelf; possesses the diverse landforms and complex spatial structure with the systems of peninsula, islands, bays, lagoons and river mouths etc. that creates enormous potential for geo-natural position resources, of which highlights are the values of coastal bays and islands. In the geo-economic position resources, Khanh Hoa coastal area has great potential to build the base for exploiting offshore resources, establish large marine economic zones, and develop the economy of marine services, especially the port - navigation and coastal ecotourism. In the geo-political position resources, this is one of leading sites for defending and protecting the country from sea, and ensuring the sovereignty and national interests in the East Sea including the direct administration of Spratly island district. The detailed investigation and assessment of the position resources in this coastal area will be an important scientific basis for the sea and island development in Khanh Hoa province.